2003
DOI: 10.1093/emboj/cdg629
|View full text |Cite
|
Sign up to set email alerts
|

The lysosomal trafficking of sphingolipid activator proteins (SAPs) is mediated by sortilin

Abstract: Most soluble lysosomal proteins bind the mannose 6-phosphate receptor (M6P-R) to be sorted to the lysosomes. However, the lysosomes of I-cell disease (ICD) patients, a condition resulting from a mutation in the phosphotransferase that adds mannose 6-phosphate to hydrolases, have near normal levels of several lysosomal proteins, including the sphingolipid activator proteins (SAPs), GM2AP and prosaposin. We tested the hypothesis that SAPs are targeted to the lysosomal compartment via the sortilin receptor. To te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
176
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(187 citation statements)
references
References 27 publications
8
176
1
2
Order By: Relevance
“…The pEGFP-sortilin WT and its truncated sortilin lacking cytoplasmic tail (pEGFP-sortilin TRU), a dominant negative mutant, were provided by Dr. Carlos R. Morales (McGill University, Hamilton, Ontario, Canada). 27 All constructs, shown in Figure 1, were confirmed by sequence analysis. These constructs have been successfully expressed in African green monkey kidney cells (Cos-7) and confirmed by Western blot analysis.…”
Section: Plasmids and Constructsmentioning
confidence: 84%
See 1 more Smart Citation
“…The pEGFP-sortilin WT and its truncated sortilin lacking cytoplasmic tail (pEGFP-sortilin TRU), a dominant negative mutant, were provided by Dr. Carlos R. Morales (McGill University, Hamilton, Ontario, Canada). 27 All constructs, shown in Figure 1, were confirmed by sequence analysis. These constructs have been successfully expressed in African green monkey kidney cells (Cos-7) and confirmed by Western blot analysis.…”
Section: Plasmids and Constructsmentioning
confidence: 84%
“…Sortilin is a newly identified lysosomal targeting receptor that is involved in the alternative sorting of the lysosomal sphingolipid activator protein prosaposin 27,28 and the GM2 activator protein. 28,29 It is a homolog of the yeast vacuolar sorting receptor Vps10p and belongs to the type I Vps10p superfamily.…”
mentioning
confidence: 99%
“…Sortilin has been widely implicated in protein delivery to the lysosome. Interestingly, some studies of sortilin lysosomal trafficking have been shown to involve GGA adaptor proteins (27,28). It is possible that directly, or indirectly, sortilin interacts with the CTFs and promotes their degradation in the lysosome.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the sortilin cytoplasmic domain can convey Golgi localization and Golgi-endosome transport. Such a sorting and trafficking role for sortilin can be attributed to two motifs, a tyrosine-based YSVL motif and an acidic clusterdileucine motif, both appearing to contribute to the endocytosis and intracellular trafficking of sortilin (27)(28)(29)(30). These motifs are likewise found within the CI-MPR (the functional equivalent of Vps10p), which is responsible for transporting lysosomal enzymes from the Golgi to the lysosome and subsequently undergoes retrograde transport via retromer (31)(32)(33).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…En effet, l'extrémité cytoplasmique de la sortiline interagit avec le domaine VHS de la protéine de tri cytosolique GGA2 (Golgilocalizing, γ-adaptin ear homology domain, ADP-ribosylation factor-binding protein) [9]. Cette interaction permet en outre à la sortiline de contribuer à l'adressage des SAP (sphingolipid activator proteins) dans les lysosomes [10]. La sortiline, en tant que protéine «cargo», ferait partie intégrante d'une machinerie intracellulaire, située principalement au niveau du réseau transgolgien, qui servirait à l'adressage de multiples protéines vers les lysosomes et autres compartiments vésicu-laires (Figure 2).…”
unclassified